Analisis Faktor-Faktor Yang Mempengaruhi Tingginya Minat Mahasiswa Berinvestasi Di Pasar Modal - Kusuma, Deden Iwan (Publikasiku, 2025)
This research examines the factors that influence the interest of STIE YKPN Yogyakarta students class 2021-2023 in investing in the capital market, including technological advances, motivation, investment knowledge, capital market socialization, investment risk, and pocket money. This research uses quantitative descriptive methods with primary data through questionnaires on STIE YKPN students class 2021–2023. The results of this research show that technological advances and capital market socialization have a positive effect on students' interest in investing. Investment risk also has a significant influence. However, motivation, investment knowledge, and pocket money were not significant. Suggestions for further research are expanding the object, adding independent variables, and increasing the number of samples.